A Framework for Addressing the Global Obesity Epidemic Locally: The Child Health Ecological Surveillance System (CHESS) - Ronald C. Plotnikoff, PhD; Penny Lightfoot, MHSA; Linda Barrett, MSc; Carla Spinola, MA; Gerry Predy, MD, FRCPC (Centers for Disease Control and Prevention, 2008)
Childhood obesity has reached epidemic levels in the developed world. Recent research and commentary suggest that an ecological approach is required to address childhood obesity, given the multidimensional nature of the problem. We propose a Canadian prototype, the Child Health Ecological Surveillance System, for a regional health authority to address the growing obesity epidemic. This prototype could potentially be used in other jurisdictions to address other child health issues. We present 8 guiding principles for the development and implementation of a regional framework for action.